2016
DOI: 10.3109/0142159x.2016.1158799
|View full text |Cite
|
Sign up to set email alerts
|

Evidence regarding the utility of multiple mini-interview (MMI) for selection to undergraduate health programs: A BEME systematic review: BEME Guide No. 37

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
120
2
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(132 citation statements)
references
References 75 publications
7
120
2
2
Order By: Relevance
“…MMIs began in McMaster University over a decade ago by adopting the format of objective structured clinical examinations (OSCEs) to the admissions interview [1], thereby incorporating a structured multi-sampling method. Previous studies have shown that MMIs offer greater validity and reliability than traditional interviews [1,2,3,4,5,6,7,8,9,10,11,12,13]. …”
Section: Introductionmentioning
confidence: 99%
“…MMIs began in McMaster University over a decade ago by adopting the format of objective structured clinical examinations (OSCEs) to the admissions interview [1], thereby incorporating a structured multi-sampling method. Previous studies have shown that MMIs offer greater validity and reliability than traditional interviews [1,2,3,4,5,6,7,8,9,10,11,12,13]. …”
Section: Introductionmentioning
confidence: 99%
“…They oversaw, for example, the prior and clear understanding of the definition of the selection criteria for each dimension, the questions to be asked, the interview structure, the previous training of the interviewers and the assessment guidelines. In truth, this is not very different from the recommendations that were recently addressed to MMI, 3,37,41 which highlight the importance of a careful and rigourous design. Equally, it is imperative to meet the need to align the vision and mission of medical schools with the students who are selected.…”
Section: 37mentioning
confidence: 62%
“…Testen krever imidlertid mye ressurser, med én intervjuer på hver stasjon. Antall stasjoner varierer vanligvis mellom 7 og 12, og intervjuene varer rundt 8 minutter (20)(21)(22). Søkerne blir testet i forskjellige problemstillinger, med fokus på hvordan de reflekterer, håndterer og eventuelt prioriterer i gitte situasjoner.…”
Section: Personlige Egenskaperunclassified